KPS-1b: The First Transiting Exoplanet Discovered Using an Amateur Astronomer's Wide-field CCD Data. (16th May 2018) - Burdanov, Artem; Benni, Paul; Sokov, Eugene; Krushinsky, Vadim; Popov, Alexander; Delrez, Laetitia; Gillon, Michael; Hébrard, Guillaume; Deleuil, Magali; Wilson, Paul A.; Demangeon, Olivier; Baştürk, Özgür; et al.
Abstract: We report the discovery of the transiting hot Jupiter KPS-1b. This exoplanet orbits a V = 13.0 K1-type main-sequence star every 1.7 days, has a mass of 1.090 − 0.087 + 0.086 M Jup and a radius of 1.03 − 0.12 + 0.13 R Jup . The discovery was made by the prototype Kourovka Planet Search (KPS) project, which used wide-field CCD data gathered by an amateur astronomer using readily available and relatively affordable equipment. Here we describe the equipment and observing technique used for the discovery of KPS-1b, its characterization with spectroscopic observations by the SOPHIE spectrograph and with high-precision photometry obtained with 1 m class telescopes. We also outline the KPS project evolution into the Galactic Plane eXoplanet survey. The discovery of KPS-1b represents a new major step of the contribution of amateur astronomers to the burgeoning field of exoplanetology.